Center of rotation locations during lumbar spine movements: a scoping review protocol. Issue 6 (20th June 2020) - Funabashi, Martha; Breen, Alex; De Carvalho, Diana; Henry, Alison; Murnaghan, Kent; Pagé, Isabelle; Wong, Arnold Y.L.; Kawchuk, Gregory
ABSTRACT: Objective: The objective of this review is to identify and map current literature describing the center of rotation locations and migration paths during lumbar spine movements. Introduction: Altered lumber spine kinematics has been associated with pain and injury. Intervertebral segments' center of rotations, the point around which spinal segments rotate, are important for determining the features of lumbar spine kinematics and the potential for increased injury risk during movements. Although many studies have investigated the center of rotations of humans' lumbar spine, no review has summarized and organized the state of the science related to center of rotation locations and migration paths of the lumbar spine during lumbar spine movements. Inclusion criteria: This review will consider studies that include human lumbar spines of any age and condition (e.g. heathy, pathological) during lumbar spine movements. Quantitative study designs, including clinical, observational, laboratory biomechanical experimental studies, mathematical and computer modeling studies will be considered. Only studies published in English will be included, and there will be no limit on dates of publication. Methods: PubMed, MEDLINE, Embase, the Cochrane Library Controlled Register of Trials, CINAHL, ACM Digital Library, Compendex, Inspec, Web of Science, Scopus, Google Scholar, and dissertation and theses repositories will be searched. After title and abstract screening of identified references, two independent reviewers will screen the full-text of identified studies and extract data. Data will be summarized and categorized, and a comprehensive narrative summary will be presented with the respective results.